2022
DOI: 10.3390/foods11081078
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Cooking Methods Affect Color, Texture and Bioactive Nutrients of Undaria pinnatifida

Abstract: Undaria pinnatifida (U. pinnatifida) is an edible brown seaweed with high health value. The objective of this study was to evaluate the effect of traditional cooking methods (i.e., blanching, steaming, boiling and baking) on the color, texture and bioactive nutrients of U. pinnatifida, so as to screen out the traditional cooking methods more suitable for U. pinnatifida. In this study, methods of blanching and boiling resulted in better reduction in total color difference (0.91 ± 0.58 and 0.79 ± 0.34, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The decrease in the hardness value of the kelp was probably due to the thermal decomposition of the polysaccharides (alginate) in the kelp cell walls, which formed a porous structure, resulting in a decrease in its hardness [ 20 ]. Similar to our results, Jiang et al found that the hardness values of Undaria pinnatifida decreased significantly after different cooking methods compared to the raw samples [ 18 ]. In addition, using artichokes, green beans, broccoli, and carrots as ingredients, Guillén et al [ 15 ] studied texture changes of these ingredients under different cooking conditions.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The decrease in the hardness value of the kelp was probably due to the thermal decomposition of the polysaccharides (alginate) in the kelp cell walls, which formed a porous structure, resulting in a decrease in its hardness [ 20 ]. Similar to our results, Jiang et al found that the hardness values of Undaria pinnatifida decreased significantly after different cooking methods compared to the raw samples [ 18 ]. In addition, using artichokes, green beans, broccoli, and carrots as ingredients, Guillén et al [ 15 ] studied texture changes of these ingredients under different cooking conditions.…”
Section: Resultssupporting
confidence: 91%
“…Both T 21 and T 22 shifted significantly to the left, indicating that the water inside the steamed kelp gradually changed to bound water, which may be related to the greater exposure of the kelp to the air during the steaming process. Similarly, Jiang et al found that the water in Undaria pinnatifida migrated towards bound water after steaming [ 18 ]. However, the T 22 peak area of the kelp treated by other methods became larger, indicating that the free water inside increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ultrasound technology was successfully used to extract phenolic acids, flavonoids, anthocyanins, and carotenoids from Morus alba leaves [ 1 ], pomegranate peels and seeds [ 2 ], guaraná by-products [ 3 ], and horchata, a Spanish beverage obtained from pressing tiger nut by-products [ 4 ]. Such side streams, rich in phenolic compounds, are often studied for their beneficial properties on human health, particularly their antioxidant properties determined in vitro [ 1 , 2 , 4 , 5 , 6 ]. The extraction of olive pomace phenolic compounds, followed by their purification using macroporous absorbing resins was also explored by Zhao et al [ 5 ], confirming the great potential as natural antioxidants, preservatives, and antimicrobials in clean-label foods.…”
mentioning
confidence: 99%
“…En el presente trabajo de Tesis el color fue determinado de manera objetiva mediante tres parámetros que toman valores continuos. Los resultados obtenidos se encuentran en el orden de los informados en wakame de diferentes regiones analizados con metodologías similares (Yamanaka y Akiyama 1993, Balbas 2012, Balbas et al 2015, Jiang et al 2022. En el experimento bifactorial, los valores de a* fueron menores (indicadores de mayor calidad) a las menores temperaturas y tiempos de cocción (65 y 75 °C y de 15 a 60 s, respectivamente).…”
Section: Colorunclassified